The Use Of Hydrology And Geology In Industrial Processing And Pit Mining In Florida - Robert O. Vernon (Society for Mining, Metallurgy & Exploration, 1966)
The discussion of water and pit mining together is most appropriate. In fact, water can be considered a mineral and a well a narrow pit. Thus, of all the mineral resources mined, water is probably the cheapest, most valuable and least valued. The delivered price, including mining, transportation, storage and marketing rarely exceeds ten cents per ton, and our economy would cease without it. The time has come when the public must recognize that the extraction of a mineral resource from the land is a necessary and inevitable result of the industries? attempt to meet the demands of a growing economy. In so much of Florida, the lands mined can, with forethought and planning, be left as improved real estate, water conservation and management lands. On the other hand, the mining industries must face up to the need for the reclamation of land and compact with themselves, appropriate governmental agencies and with the mining states to restore mined lands to usefulness. Of limestone, sand, and clay 90 to 100 percent of the mined material is used, but with planning and specing, these pits, if they penetrate the water table, become valuable as real property. Phosphate, which returns about 70 percent of the mined materials to the pit, can reclaim the land for many purposes.